(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
This article analyzes the strategic importance and relevance of implementing modern information technologies within the state border protection system. It highlights the role of the “Smart Border” concept, artificial intelligence, unmanned aerial systems, geographic information systems, biometric identification, and big data analytics in enhancing border security frameworks.